Le sentir : au fondement du politique - Catherine Grout (Projets de Paysage)
In this text, I explain how the notion of sensing (sensory experience ) according to Erwin Straus (which differs from the notions of sensation and perception) comprises the political perspective of a landscape project and how this postulate is applied in my teaching method for undergraduates in landscape architecture. A key question is the consideration of quality of presence in relation to oneself and the world. This makes it possible to communicate with other people on the basis of a common ground with a political horizon and supports the acceptance of difference and plurality. By means of concrete supporting elements linked to theoretical references and methods (requiring experimentation and trial and error) the students are encouraged to make the distinction between sensing and perception. These two notions then inspire their selected projects through an embodied political horizon. Based on their texts and classroom activities, I present the benefits and drawbacks inherent to this teaching method focusing on spatiality.